Multidrug-resistant tuberculosis clusters and transmission in Taiwan: a population-based cohort study - Liu, Kuang-Hung; Xiao, Yu-Xin; Jou, Ruwen (Frontiers in Microbiology, 2024)
Multidrug-resistant tuberculosis (MDR-TB) remains a challenge in the TB program of Taiwan, where 0.5% of new cases and 2.1% of previously treated cases were resistant to at least rifampin (RIF) and isoniazid (INH). Since >80% of our MDR-TB are new cases, genotyping of MDR Mycobacterium tuberculosis is implemented to facilitate contact investigation, cluster identification, and outbreak delineation. This is a population-based retrospective cohort study analyzing MDR-TB cases from 2019 to 2022. Whole genome sequencing (WGS) was performed using the Illumina MiSeq and analyzed using the TB Profiler. A single nucleotide polymorphism (SNP) threshold of ≤12 and phylogenetic methods were used to identify putative transmission clusters. An outbreak was confirmed using genomic data and epidemiologic links. Of the 297 MDR-TB cases, 246 (82.8%), 45 (15.2%), and 6 (2.0%) were simple MDR, extensively drug-resistant tuberculosis (pre-XDR-TB) and extensively drug-resistant tuberculosis (XDR-TB), respectively. The sublineage 2.2 - modern Beijing was the predominant (48.8%) MDR-TB strain in Taiwan. Phylogenetic analysis identified 25.3% isolates in 20 clusters, with cluster sizes ranging from 2-13 isolates. Nevertheless, only 2 clusters, one household and one community, were confirmed as outbreaks. In this study, we found that males had a higher risk of MDR-TB transmission compared to females, and those infected with the sublineage 2.1-proto-Beijing genotype isolates were at a higher risk of transmission. Furthermore, 161 (54.2 %) isolates harbored compensatory mutations in the rpoC and non- rifampicin resistant determinant region (non-RRDR) of the rpoB gene. MDR-TB strains containing rpoB S450L and other compensatory mutations concurrently were significantly associated with clusters, especially the proto-Beijing genotype strains with the compensatory mutation rpoC E750D or the modern Beijing genotype strains with rpoC D485Y/ rpoC E1140D. Routine and continuous surveillance using WGS-based analysis is recommended to warn of risks and delineate transmission clusters of MDR-TB. We proposed the use of compensatory mutations as epidemiological markers of M. tuberculosis to interrupt putative MDR-TB transmission.